Sexual Health Education Based on the Theory of Planned Behavior to Prevent Risky Sexual Behavior in Adolescents: A Systematic Review - Stephani Dwiyana Putri; Shrimarti Rukmini Devy; Ira Nurmala; Andi Safutra Suraya (GLOBAL HEALTH SCIENCE GROUP, 2024)
Risky sexual behavior is a serious issue as it is a major risk factor for the emergence of diseases such as Sexually Transmitted Infections (STIs), disabilities, and mortality among adolescents due to a lack of information about sexual health. The aim of this study is to prevent risky sexual behavior through health education based on the Theory of Planned Behavior (TPB). A systematic review was conducted using four electronic databases (Scopus, PubMed, Web of Science (WoS), and Science Direct) on previous studies employing cross-sectional, quasi-experimental, and Randomized Control Trials (RCT) designs from the last 5 years (2017-2021). The database search was performed from November to December 2021. The Joanna Briggs Institute (JBI) was used as a guide for assessing the quality of the studies, and PRISMA was used as the research guideline. Data analysis utilized descriptive analysis to identify themes. There were 11 articles that met the inclusion criteria in the review. All selected studies discussed sexual health education using the TPB approach. There was an improvement in behavior change based on TPB (attitudes, subjective norms, control, and intention) among adolescents who received sexual health education. The factors influencing adolescents' intentions are closely related to the process of behavior formation. These factors include attitudes, subjective norms, and behavioral control. A Sexual health education based on TPB can be an appropriate intervention to prevent risky sexual behavior among adolescents, as its priority is to strengthen behavioral intentions by enhancing attitudes, subjective norms, and behavioral control through continuous health education.